The Role of Nonsteroidal Anti-inflammatory Drugs in the Prevention of Post Endoscopic Retrograde Cholangiopancreatography Pancreatitis - Sheikh, Imran; Fontenot, Eric; Waghray, Nisheet; Ismail, Mohammad K; Tombazzi, Claudio; Smith, J Lacey (JOP. Journal of the Pancreas, 2014)
Post-ERCP pancreatitis (PEP) is the most common major complication associated with ERCP. Beginning with an overview of the risk factors for the development of PEP, this review introduces the mechanism of injury in PEP and the role of pharmacological prevention. NSAIDs are increasingly found to offer prevention against the development of PEP, and their mechanism and supportive data are summarized, especially in relationship to the practice of prophylactic pancreatic duct stenting. Image: University of Tennessee Health Science Center. Memphis, TN, USA.